Mindfulness en el síndrome de intestino irritable - Beltrán M., Caroll; Iribarne W., Catherine; Valenzuela M., Felipe; Navea S., César; Pérez de Arce O., Edith; Madrid S., Ana María (Revista Hospital Clínico Universidad de Chile, 2016)
The Irritable Bowel Syndrome (IBS) is a functional digestive disorder recognised as a Biopsychosocial model, because psychological, social and biological factors influence the development of its symptomatology. A high psychiatric comorbidity is frequently observed in patients with IBS associated to an increase in the severity of symptoms and a low-grade of inflammatory response. Although its pathophysiological mechanism has not been fully understood, an imbalance in bidirectional communication is described in the gut-brain axis that affects psychoneuroimmune status of IBS patients. Diverse psychotherapeutic interventions have been shown to be effective in reducing the psychosocial impact in IBS patients, as well as in reducing their intestinal symptoms. However, at the clinical practice, it is not routinely applied because of its high cost. The Mindfulness-Based Stress Reduction (MBSR) is an alternative program that shown to be effective in reducing the clinical severity and improving the quality of life of patients with IBS. Although MBSR has demonstrated to reduce the levels of pro-inflammatory cytokines, including IL-6, in healthy subjects and cancer’s patients, its effect on the immune response in IBS patients remains unknown. This review discusses the pathophysiological mechanisms underlying the relationship between psychosocial disturbances, clinical symptomatology and low-grade inflammation in IBS. Based on that, we present the arguments that allow proposing the use of MBSR for the IBS treatment.